Evaluating governance structures in the implementation of early childhood policies: A pathway to sustainable development - Merino, Ana Lucia Ravines; Zavaleta, Jose Manuel Armas; Manrique, Antony Mejia; Mejia, Percy Junior Castro (Edelweiss Applied Science and Technology, 2025)
The evaluation of general governance structures plays a crucial role in the implementation of early childhood policies, serving as a fundamental pillar for sustainable development. This study aimed to analyze the relationship between governance structures and the effectiveness of policies directed at child welfare in less sustainable rural communities in the Peruvian high-lands. The research was conducted with a sample of 260 officials and key stakeholders involved in the management and execution of these policies in the central highlands region of Peru. The study design was quantitative, non-experimental, cross-sectional, and correlational in scope. Da-ta were collected using structured questionnaires that measured the perceptions of stakeholders regarding governance and its impact on early childhood policy outcomes. The data were ana-lyzed using the Spearman Rho test, yielding a correlation coefficient of r=0.528 and a significance level of p=0.003. These results allowed for the rejection of the null hypothesis and confirmed that governance structures have a significant impact on the effectiveness of early childhood policies. The instruments used to measure the variables demonstrated high reliability, with Cronbach’s alpha coefficients of 0.91 for governance and 0.80 for policy implementation effectiveness. The findings underscore that adopting inclusive and well-articulated governance structures can sub-stantially improve early childhood policy outcomes, promoting comprehensive development in children and strengthening the foundations for sustainable development, especially in rural communities with resource limitations.